2019
DOI: 10.4300/jgme-d-19-00760.1
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Graduate Medical Education Diversity and Inclusion

Abstract: , the Accreditation Council for Graduate Medical Education (ACGME) Board of Directors formed a planning committee to assess the state of diversity and inclusion in the graduate medical education (GME) space. The planning committee set the following as its charge: & Consider current practices in US GME focused on enhancing the clinical learning environment as it pertains to diversity and inclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 1 publication
(1 reference statement)
0
25
0
Order By: Relevance
“…8,32 Moreover, the participants' selection criterion used in this study disregarded racial/ethnicity disparity in residency withdrawn/dismissed rates. 33 Finally, medical knowledge assessment was confined to exam performance.…”
Section: Discussionmentioning
confidence: 99%
“…8,32 Moreover, the participants' selection criterion used in this study disregarded racial/ethnicity disparity in residency withdrawn/dismissed rates. 33 Finally, medical knowledge assessment was confined to exam performance.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of educating future doctors of diverse backgrounds, the creation of educational pipeline programs at various medical education levels has been developed to help all trainees in medicine obtain the support they need to become physicians. 46 Many specialty GME training programs have implemented strategies to enhance the recruitment of URiM physicians. 46 Beyond these 2 efforts, medical schools, and GME programs are also adopting holistic review methodologies when screening trainee applications.…”
Section: Diversity Equity and Inclusionmentioning
confidence: 99%
“…In a study of UIM residents treatment in the workplace, Oseeo-Asare et al 25 found that UIM residents more often deal with daily microaggressions and biases. The ACGME also acknowledged the need to protect all residents, 26 particularly those identifying from UIM backgrounds, and added requirements, which not only address program and institutional standards to increase diversity recruitment and retention efforts, but also require that institutions maintain safe and respectful clinical learning environments (Section VI.B.6). 26,27 Programs should ensure that these protections are in place by creating reporting processes for trainees and faculty to raise concerns.…”
Section: Retentionmentioning
confidence: 99%